Advances in 3D Bioprinting for Development of Next Generation Dermal Fillers and Cosmetic Implants. - D. Phupate, Narendrakumar; G. Kadam, Sanika; R. Tathe, Sanika; P. Bhagat, Sanjana; V. Tanpure, Sanjivani; D. Paulbuddhe, Shraddha (Journal of Neonatal Surgery, 2025)
3D bioprinting, also known as additive manufacturing, is an innovative technology that is changing the way we approach biomedical applications. It brings together fields like engineering, manufacturing, art, education, and medicine to create new possibilities. This process uses living cells combined with materials that are safe for the body to design tissue or organ models in place for use inside the body. In dermatology, 3D bioprinting is transforming the way we think about skin treatments by offering new ways to engineer tissues and perform aesthetic repairs. This study looks at the latest developments in 3D bioprinting for making next generation dermal fillers and cosmetic implants that are better than traditional synthetic fillers. Unlike regular materials, bio-printed fillers contain living cells and safe biomaterials, making them more compatible with the body, safer, and offering longer-lasting results. The process involves using a special type of ink made from fibroblasts, keratinocytes, and parts of the extracellular matrix. These are printed layer by layer to create structures that look very similar to natural skin. These new fillers not only restore volume but also help in regenerating tissues, producing collagen, and improving how skin functions. In dermatology, these advancements have big applications in anti-aging treatments, fixing scars, healing wounds, and reconstructing soft tissues. Bio-printed cosmetic implants offer a more personalized solution since they can be made to fit individual needs using advanced imaging and computer design tools. However, there are still challenges such as high costs, technical difficulties, and the need for regulatory approval. Despite these, ongoing research is helping to bring these technologies into clinical use. The novelty of this study is the shift from using temporary cosmetic solutions to living, patient-specific, and regenerative dermal fillers and implants. This marks a major change in dermatology where treatments go beyond just looking better and actually help restore and renew skin tissues.. .